An updated national survey of triage and triage related work in Sweden: a cross-sectional descriptive and comparative study - Sara C. Wireklint; Carina Elmqvist; Katarina E. Göransson (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2021)
Abstract Background Triage and triage related work has been performed in Swedish Emergency Departments (EDs) since the mid-1990s. According to two national surveys from 2005 to 2011, triage was carried out with different triage scales and without guidelines or formal education. Furthermore, a review from 2010 questioned the scientific evidence for both triage as a method as well as the Swedish five level triage scale Medical Emergency Triage and Treatment System (METTS); nevertheless, METTS was applied in 65% of the EDs in 2011. Subsequently, METTS was renamed to Rapid Emergency Triage and Treatment System (RETTS©). The hypothesis for this study is that the method of triage is still applied nationally and that the use of METTS/RETTS© has increased. Hence, the aim is to describe the occurrence and application of triage and triage related work at Swedish Emergency Departments, in comparison with previous national surveys. Methods In this cross-sectional study with a descriptive and comparative design, an electronic questionnaire was developed, based on questionnaire from previous studies. The survey was distributed to all hospital affiliated EDs from late March to the middle of July in 2019. The data was analysed with descriptive statistics, by IBM SPSS Statistics, version 26. Results Of the 51 (75%) EDs partaking in the study, all (100%) applied triage, and 92% used the Swedish triage scale RETTS©. Even so, there was low concordance in how RETTS© was applied regarding time frames i.e., how long a patient in respective triage level could wait for assessment by a physician. Additionally, the results show a major diversion in how the EDs performed education in triage. Conclusion This study confirms that triage method is nationally implemented across Swedish EDs. RETTS© is the dominating triage scale but cannot be considered as one triage scale due to the variation with regard to time frames per triage level. Further, a diversion in introduction and education in the pivotal role of triage has been shown. This can be counteracted by national guidelines in what triage scale to use and how to perform triage education.